The Legend of Sidi Rabah Bouqabrin (he has two graves) in the Al-Wancharis region a sociohistorical reading- - bouchama, ahamed; kerais, eldjilali (Journal of Social Sciences and Humanities, 2023)
This paper attempts to study one of the legends known in the Region of El-Wancharis, its main hero, Sidi Rabah Boukabrin, by clarifying its roots of ethnic and geographical elements, historical accumulations, popular heritage, and religious beliefs, in order to work to dismantle this legend, highlighting its intersections that link reality to fiction, the past to the present, and rituals with its legislation, and this in order to better understand the reasons why the phenomenon of Righteous has a large area of the interests of the local human being, even formed his religious identity, his collective memory and became the image of the Pious (Wali) in his eyes linked to dignity, and the terrible ability that resembles what the Totem had in primitive societies, and thus turning the Pious Righteous into a supernatural man, he can do many metaphysical phenomena, such as controlling the forces of nature, or returning after death, and inflicting curse and punishment, hence the body of this situation in The surroundings of the legend are a distinct reality, forming a hierarchical society that has made the descendants of the Pious and his followers, the masters of society, and his reference.